High Altitude, High Energy Demand: Evolved Strategies for Energy Intake in Deer Mice - Chau, Vicky (My University, 2025)
High-altitude environments present a unique set of challenges such as cold temperatures, low oxygen availability, and limited food resources. Due to high rates of heat loss, eutherian animals must continuously replenish their energy stores to sustain the metabolic demands of thermoregulation. However, the mechanisms through which high-altitude species, like the North American deer mouse (Peromyscus maniculatus), acquire sufficient energy to meet these demands remain unclear. The objective of my thesis was to investigate how the digestive strategies of high-altitude animals have evolved to support their elevated energetic requirements. My findings demonstrated that under chronic cold hypoxic exposure, high-altitude populations significantly increased energy intake by consuming more food leading to an increase in energy absorption. Interestingly, high-altitude deer mice did not differ from low-altitude populations in their gut passage time. However, a key distinction emerged when looking at body composition and digestive efficiency, where high-altitude deer mice maintained lean mass and digestive efficiency, whereas low-altitude individuals did not – suggesting that low-altitude populations struggled to cope with cold hypoxic exposure. Additionally, changes indicative of altered glucose and lipid handling were observed, pointing towards differences in macronutrient absorption as well as in total energy extraction. This research provides new insights into the digestive adaptations of high-altitude deer mice, shedding light on their capacity to acquire and process energy efficiently in extreme environments.
Keywords: High Altitude; Hypoxia; Digestive Efficiency; Nutrient Absorption